Metode Supervisi Akademik Kepala Sekolah Terhadap Guru Pendidikan Agama Islam - Nurhudha Sandi Utomo (Program Studi Manajemen Pendidikan, 2019)
This study aims to describe the methods and steps of academic supervision of the principal of the Muhammadiyah Plus Salatiga Middle School in improving the performance of PAI learning teachers. This research uses a qualitative ethnographic approach to education. Data collection techniques through observation, documentation and interviews. While the data analysis of this study uses inductive qualitative. The results of this study concluded that the academic supervision method applied to improve teacher performance is a collaborative method, namely the direct and indirect methods. Supervision techniques used, using two techniques, namely individual and group techniques. Individual techniques include: class visits, observations and individual meetings. Group techniques by holding teacher meetings and training to improve teacher competency. The steps are as follows: 1) Planning documents; 2) Implemented after there is socialization and agreement with the teacher to be supervised; 3) Conduct an analysis of the implementation of supervision; 4) Providing feedback from the results of the supervision analysis; 5) A follow-up plan for supervision is carried out; 6) Prepare reports on the results of supervision.